1998
DOI: 10.1037/0022-0167.45.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Internal working models, self-reported problems, and help-seeking attitudes among college students.

Abstract: A person's internal working models of close relationships (J. Bowlby, 1988) incorporate 2 discrete yet interrelated cognitive schemas: a self model containing perceptions of one's own worth and lovability and an other model embodying core expectations about the trustworthiness and dependability of intimate others in one's social world. This study tested hypothesized interrelationships, in a college-student sample, (a) between self-model differences and self-reported problems and (b) among other-model differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
94
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 26 publications
12
94
2
2
Order By: Relevance
“…The measure has been found to detect preferences in college students' intent to seek mental health services (Cash et al, 1975). The ISCI has also been found to be associated with the significance of a current problem (Lopez, Melendez, Sauer, Berger, & Wyssmann, 1998). Adequate internal consistency estimates have been present across studies (.84-.95; Kelly & Achter, 1995;Lopez et al, 1998;Solberg, Ritsma, Davis, Tata, & Jolly 1994).…”
Section: Methodsmentioning
confidence: 94%
“…The measure has been found to detect preferences in college students' intent to seek mental health services (Cash et al, 1975). The ISCI has also been found to be associated with the significance of a current problem (Lopez, Melendez, Sauer, Berger, & Wyssmann, 1998). Adequate internal consistency estimates have been present across studies (.84-.95; Kelly & Achter, 1995;Lopez et al, 1998;Solberg, Ritsma, Davis, Tata, & Jolly 1994).…”
Section: Methodsmentioning
confidence: 94%
“…In the current sample, the internal consistency of the Psychological and Interpersonal Concerns subscale was .90. The ISCI has been found to detect variation in college student's' intent to seek counseling on the basis of counselor attractiveness (Cash et al, 1975), correlate with the perceived significance of a current problem among those with a positive working model of others (Lopez et al, 1998), and mirror general attitudes toward seeking help (r ϭ .36; Kelly & Achter, 1995). As before, three parcels were created from the interpersonal subscale to represent the observed indicators of intentions to seeking counseling for psychological and interpersonal concerns.…”
Section: Methodsmentioning
confidence: 99%
“…Both Feeney and Ryan (1994) and have reported that those with higher levels of attachment avoidance report less intention to seek psychological help. In addition, Lopez et al (1998) found that, among individuals experiencing psychological problems, those with a negative model of others (i.e., high levels of attachment avoidance) were less willing to seek counseling than those with positive models of others. These tendencies have also been found in day-to-day support interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Women were more receptive and have higher positive attitudes compared to men (Lopez, Melendez, Sauer, Berger, & Wyssmann, 1998;Vogel, Wade, Wester, Larson, & Hackler, 2007;Greenidge, 2007). For instance, Kano (city in Nigeria) female students in tertiary institutions preferred to seek help from expert guidance in resolving their problem while male students' preferred non-expert guidance (Kolo, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%